Characterization and isolation of anti-HIV and latency reversal agents for the development of a herbal mixture of Gnidia sericocephala, Senna italica, Sclerocarya birrea and Pentanisia prunelloides - Maharaj, Vinesh J. (University of Pretoria, 2023)
Thesis (PhD)--University of Pretoria, 2022.